Australian Children’s Literature and Postcolonialism: A Review Essay - Daozhi Xu (Ilha do Desterro)
The theme of land and country is resonant in Australian children’s literature with Aboriginal subject matter. The textual and visual narratives present counter-discourse strategies to challenge the colonial ideology and dominant valuation of Australian landscape. This paper begins by examining the colonial history of seeing Australia as an “empty space”, naming, and appropriating the land by erasing Aboriginal presence from the land. Then it explores the conceptual re-investment of Aboriginal connections to country in the representation of Australian landscape, as reflected and re-imagined in fiction and non-fiction for child readers. Thereby, as the paper suggests, a shared and reconciliatory space can at least discursively be negotiated and envisioned.